Children, spousal love, and happiness: An economic analysis - Shoshana Grossbard-Shechtman; Sankarananda Mukhopadhyay (Institute for the Study of Labor (IZA), 2012)
In this paper we examine how children affect happiness and relationships within a family by analyzing two unique questions in the National Longitudinal Study of Youth's 1997 cohort. We find that (a) presence of children is associated with a loss of spousal love; (b) loss of spousal love is associated with loss of overall happiness; but (c) presence of children is not associated with significant loss of overall happiness. If children reduce feelings of being loved by the spouse but do not reduce reported happiness even though spousal love induces happiness, then it must be the case that children contribute to parental happiness by providing other benefits. After ruling out some competing compensation mechanisms we infer that loss of spousal love is compensated with altruistic feelings towards children.
Keywords: J13; D10; 330; children; happiness; emotions; marriage; religion; Zufriedenheit; Kinder; Ehe; Religion; Familienökonomik; Schätzung; USA